CHEMICAL AND SENSORY CHARACTERISTIC OF SORGHUM (Sorghum bicolor) TAPAI WITH TRADITIONAL PACKAGING - Andre Yusuf Trisna Putra; Rosida Rosida; Khoirul Azmir (Food ScienTech Journal, 2019)
Tapai is one of the traditional food from Java island. Nowadays, traditional food is being ignored by people. Conserving traditional foods are needed. Processing into a variety of foods that has good nutrition can make traditional food exist. Sorghum (Sorghum bicolor)is a good source of carbohydrates, fibers, phenolic compounds, and antioxidant. However, it has not been fully utilized. Bitter taste, sandy texture and unpleasant aroma in sorghum cause people do not like. Therefore, this study aimed to develop tapai from sorghum. This study will focus on the evaluation of starch content, pH, acidity content, sugar content and sensory evaluation tapai made from varieties of sorghum and types of natural packaging. The method used in this study was the experimental method using a completely randomized factorial design consisting of two factors, variable of sorghum (white, red and brown sorghum) and types of natural packaging (banana leaf, pandanus leaf, and guava leaf) with two replications. Duncan's multiple range tests were performed with a 5% significance for statistical analysis. Results revealed that the highest starch content was 27,4% in tapai from brown sorghum with banana leaf packaging. Regarding sugar content, tapai from brown sorghum with banana leaf packaging had the highest result. Whereas, based on sensory evaluation, tapai from white sorghum with banana leaf packaging was the most favored by panelists.